TRIPLE HELIX DAN PERKEMBANGAN INOVASI DAERAH, TINJAUAN TERHADAP PERAN AKUNTANSI DALAM KEBERLANJUTAN IKM - Arifah, Siti; Purnomo, Rochmat Aldy; Asmara, Anugerah Yuka; Kusumawardhani, Dhian; Santoso, Adi ((JRAMB) Jurnal Riset Akuntansi Mercu Buana, 2025)
Regional Innovation System (SIDa) plays a crucial role in enhancing knowledge-based economic competitiveness at the regional level. This study employs a Systematic Literature Review (SLR) approach to explore the concept of the Triple Helix in advancing regional innovation and the role of accounting in strengthening small and medium-sized enterprises (SMEs). Through a review of existing literature, this research aims to identify the interactions between academia, government, and industry in creating an inclusive and sustainable innovation ecosystem. The study finds that the success of the Triple Helix collaboration depends on the role of government as a facilitator, universities as sources of innovation, and SMEs as users of technology. The Triple Helix model provides a strong conceptual foundation for understanding and developing an effective SIDa. A successful SIDa heavily relies on strong synergy and collaboration among universities, industry, and government at the regional level. Accounting can empower SMEs by providing sound business knowledge, which is essential for building partnerships and accessing funding. Accounting thus serves as a critical foundation for the growth and sustainability of SMEs within the regional innovation ecosystem. This article is expected to contribute to the formulation of strategic policies aimed at strengthening SIDa through a collaborative approach.